Inflation Everywhere is a Monetary Phenomenon: An Introductory Note (The Pakistan Development Review, 2006)
Ever since the 1970s, when inflation became a virtually global phenomenon, controlling inflation has become a high priority for policy-makers. Given the well-known costs of inflation, policy now in all countries is inflation-averse. Perhaps one of the more important adverse consequences of inflation may be that high and persistent inflation is a regressive tax1 which adversely impacts the poor.2 The poor are extremely limited in their options to protect themselves against inflation; they are normally asset-poor, while most of their saving is in the form of cash. Inflation erodes cash savings and protects the rich who hold real assets.3 It is not surprising that inflation may be politically costly for the government. Studies have also found that high and volatile inflation has been detrimental to growth and financial sector development. Resource allocation is inhibited as inflation obscures relative price changes and thus inhibits optimal resource allocation. For policy to control inflation, it is important to understand the factors that drive inflation. Unquestionably, empirical evidence points to “inflation being always and everywhere a monetary phenomenon” [Friedman (1963)]. However, there still remains some debate on whether supply-side factors could cause inflation without monetary accommodation.4 The structuralist school of thought holds that supply constraints that drive up prices of specific goods can have wider repercussions on the overall price level. Similarly, there are a number of possible sources of rising costs such as wages, profits, imported inflation-exchange rate, commodity prices, external shocks, exhaustion of natural resources, and taxes. For example, in Pakistan, increases in the wheat support price have frequently been blamed for increasing inflation.5 ........